HIV outcomes at a Canadian remand centre. Issue 3 (12th September 2016) - Subramanian, Yazhini; Khan, Muhammad Naeem; Berger, Sara; Foisy, Michelle; Singh, Ameeta; Woods, Dan; Pyne, Diane; Ahmed, Rabia
Abstract : Purpose: The purpose of this paper is to assess the impact of short-term incarceration on antiretroviral therapy (ART) adherence, virologic suppression, and engagement and retention in community care post-release. Design/methodology/approach: A retrospective chart review of patients who attended the human immunodeficiency virus (HIV) Outreach Clinic at a Canadian remand center between September 2007 and December 2011 was carried out. Data extraction included CD4 lymphocyte count, HIV viral load, ART prescription refills, and community engagement and retention during and one-year pre- and post-incarceration. Findings: Outpatient engagement increased by 23 percent ( p =0.01), as did ART adherence (55.2-70.7 percent, p =0.01), following incarceration. Retention into community care did not significantly improve following incarceration (22.4 percent pre-incarceration to 25.9 percent post-release, p =0.8). There was a trend toward improved virologic suppression (less than 40 copies/ml; 50-77.8 percent ( p =0.08)) during incarceration and 70. 4 percent sustained this one-year post-incarceration ( p =0.70). Originality/value: The impact of short-term incarceration in a Canadian context of universal health coverage has not been previously reported and could have significant implications in optimizing HIV patient outcomes given the large number of HIV-positive patients cycling through short-term remand centers.